Analisis Pembiayaan Konsumen Dan Penarikan Kendaraan Debitur Yang Wanprestasi Pasca Putusan Mahkamah Konstitusi Nomor 18/Puu-Xvii/2019 (Penelitian Di PT Mega Central Finance Kota Medan) - Hendra Wijaya (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2022)
Consumer financing is one of the facilities that make it easier for everyone to own a vehicle. In the process of implementing the consumer financing in multi-finance companies, it is possible for the occurrence of default by the debtor. In practice, if the debtor defaults in fulfilling his obligations, the consumer financing companies can execute the financed vehicle using a fiduciary. After the decision of the Constitutional Court Number 18/PUU-XVII/2019, all executions of fiduciary guarantees must go through a court decision except on the basis of the will and the own approval from the debtor. As for the formulation of the problem to be discussed and studied further is related to the legality of the consumer financing, especially the vehicles according to applicable legal provisions, the legal mechanism for the withdrawal of the vehicle of the debtor in default and the legal effort for the creditors of PT Mega Central Finance after the verdict of the Constitutional Court Number 18/PUU-XVII/ 2019 in consumer financing and the withdrawal of the vehicle of the debtor in default.Keywords : consumer financing, creditors, default.